Axial behaviour of precast concrete panels with hollow composite reinforcing systems. (August 2021) - Al-Fakher, Usama; Manalo, Allan; Alajarmeh, Omar; Aravinthan, Thiru; Zhuge, Yan; Bai, Yu; Edoo, Azam
Abstract: This study investigated the axial behaviour of precast concrete panels with hollow composite reinforcing systems (CRSs). These systems were provided to create voids, reduce the concrete and the self-weight of the panels. Thirteen specimens representing the unit width of a precast concrete panel were prepared and tested under concentric axial compression to investigate the effects of CRS spacing and slenderness ratio. From the experimental results, introducing the hollow core did not affect the stiffness of the panels due to the relatively small area of the hollow core at the middle of the section, while the axial capacity was reduced by 11%. On the other hand, the CRS increased the axial strength capacity and stiffness of the hollow panels by 70% and 71%, respectively as it provided additional reinforcement and stabilised the concrete core. Furthermore, narrower CRS spacing provided better structural performance than wider spacing due to the higher efficiency of the CRS and its flanges in holding together the cracked concrete. Moreover, the axial stiffness provided by the CRS prevented the global buckling failure of slender panels. Finally, a theoretical model was developed to predict axial load capacity by considering the contribution of the CRS and slenderness of the panels.